Ultimate flexural strength analysis of composite slim floor beam. Issue 10 (July 2021) - Xia, Yuanxin; Han, Chunxiu; Zhou, Donghua; Wang, Yonghui; Wang, Peng
This paper presents a new type of composite slim floor beam, determined by combining the results of an experimental study and theoretical analysis of the ultimate flexural strength of slim floor beams. The shear connectors play a significant role in the mechanical properties of this type of composite slim floor beam, because the precast concrete slab is laid on the bottom flange of the steel section and because the upper portion of the steel beam is encased in the cast-in-place concrete slab. To investigate the ultimate flexural strength, three specimens, which included headed studs, transverse steel bar shear connectors and no shear connectors, were tested. Additionally, a detailed numerical analysis was performed to verify the experimental results, which indicated that a higher-strength steel beam and thicker concrete slab can effectively enhance the stiffness and flexural capacity of the composite slim floor beam. Based on plastic mechanics and limit analysis theory, a calculation method was derived to estimate the ultimate flexural strength of a composite slim floor beam, and a comparison between the calculation and experimental results shows that the theoretical results exhibit good agreement with the experimental results, and the proposed analysis method can be used in future studies to gain a better understanding of the ultimate flexural strength of composite slim floor beams.